Advisory, Collaborative and Scrutinizing Roles of Deliberative Mini-Publics - Setälä Maija (Frontiers Media, 2022)
The normative point of departure in this article is that mini-publics can “complement”
representative democracy only if they enhance inclusive processes of mutual justification
among elected representatives who are responsible for public decisions. This article
distinguishes three different roles of mini-publics in representative decision-making. Minipublics
can be 1) advisory when they provide input for collective will-formation in the
representative arena, 2) collaborative when they involve elected representatives in the
deliberative process, 3) scrutinizing when they check representative decision-making. The
article analyzes strengths and weaknesses of these roles of mini-publics. Advisory minipublics
are particularly vulnerable to “cherry-picking.” While collaborative uses of minipublics
may facilitate inclusive reason-giving among elected representatives, they entail
risks of representative dominance. Scrutinizing use of mini-publics seem particularly
promising from the normative perspective, but it requires a well-defined institutional
framework. The article concludes that while there are ways to avoid problems
emerging in these different roles, political context is crucial in terms of the deliberative
impact of mini-publics.